ADMINISTRATIVE AND LEGAL ASPECTS OF LICENCING IN HIGHER EDUCATION - Oleksiy Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2019)
The study provides an insight into administrative and legal aspects of licensing higher educational institutions, analyses changes in the licensing system of higher educational institutions and examines measures aimed at nhancing the role of this institution in addressing the problem of quality assurance of higher educational institutions. The author investigates the legal nature and administrative aspects of licensing in higher education and proves that licensing in higher education is an administrative procedure, which takes into account the specific nature and characteristics of the activities of an educational institution, that are stipulated by the corresponding regulatory documents. The paper determines licensing as a legal phenomenon, which means that licensing activity belongs to the system of state-executive relations, the core of which is the organizing the citizens and the legal entities' activities in the spheres where steadfast adherence to definite requirements and certain legal behavior is expected. One of the key research questions of this paper was the ambiguity of the concept of licensing in scientific literature, which combines the norms of administrative and civil law. Social and legal functions of licensing higher education institutions with the aim of their effective functioning in social and legal environment are outlined. Further, the author identifies the characteristic features of licensing in education. This article also address the research questions of licensing in education and offers the conclusions regarding the features of licensing as a legal phenomenon. The role of licensing activity in the system of state-executive relations and its contents and constituents are determined.